2013
DOI: 10.1371/journal.pone.0065704
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticles Induce Necrosis and Apoptosis in Macrophages in a p47phox- and Nrf2-Independent Manner

Abstract: In view of the steadily increasing use of zinc oxide nanoparticles in various industrial and consumer applications, toxicological investigations to evaluate their safety are highly justified. We have investigated mechanisms of ZnO nanoparticle-induced apoptosis and necrosis in macrophages in relation to their important role in the clearance of inhaled particulates and the regulation of immune responses during inflammation. In the murine macrophage RAW 264.7 cell line, ZnO treatment caused a rapid induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
72
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 57 publications
7
72
1
Order By: Relevance
“…34 However, Wilhelmi et al reported that ZnO NPs induce necrosis and apoptosis in macrophages via ROS-and p53-independent pathway. 24 Consistent with the latter study, we found that both SiO 2 and ZnO NPs induced apoptosis in U373MG cells, which express mutant p53. Other authors have suggested that, in addition to the ROS-mediated p53 activation pathway, SiO 2 and ZnO NPs may activate the p38 mitogen-activated protein kinase and/or c-Jun N-terminal kinase pathways to transactivate proapoptotic genes and induce apoptosis.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…34 However, Wilhelmi et al reported that ZnO NPs induce necrosis and apoptosis in macrophages via ROS-and p53-independent pathway. 24 Consistent with the latter study, we found that both SiO 2 and ZnO NPs induced apoptosis in U373MG cells, which express mutant p53. Other authors have suggested that, in addition to the ROS-mediated p53 activation pathway, SiO 2 and ZnO NPs may activate the p38 mitogen-activated protein kinase and/or c-Jun N-terminal kinase pathways to transactivate proapoptotic genes and induce apoptosis.…”
supporting
confidence: 90%
“…[20][21][22][23] However, a recent study found that ZnO NPmediated apoptosis was not related to ROS generation or the p53 pathway. 24 Thus, the cell-death pathways mediated by SiO 2 and ZnO NPs are still the subject of some debate. In this study, we investigated the cytotoxic effects of SiO 2 and ZnO NPs on the U373MG human glioblastoma cell line.…”
Section: Introductionmentioning
confidence: 99%
“…10,34,35 The observed toxicities have been linked to their physicochemical properties, such as dissolution into ionic Zn and their ability to generate ROS. 36 Consequently, these same properties have been exploited in the development of nanomedicines.…”
Section: Discussionmentioning
confidence: 99%
“…RAW264 cells are one of the classical macrophage models and have been often used for studying the effects of nanoparticles in macrophages (e.g. in 26,[28][29][30][31][32][33] . They are also one of the few cell lines able to produce NO upon LPS stimulation 34 , a feature absent from the other classical human macrophage model THP-1.…”
Section: Introductionmentioning
confidence: 99%